EXAMINING OF THE RELATIONSHIP BETWEEN INDIVIDUALS TAKING PCR TESTS AND THEIR RELATED COVID-19 ANXIETY - Gökhan Aba; Havvanur Karataş Koç (International Journal of Health Services Research and Policy, 2025)
This study examines the relationship between individuals' COVID-19-related anxiety and their PCR testing behaviour. The pandemic has had a significant impact on mental health, increasing health-related anxiety, which includes excessive fear of illness. It is important to understand how anxiety affects PCR testing behaviour. The study was conducted in Trabzon, Turkey, with 400 participants aged 18 years and older, using face-to-face interviews. Variables such as age, gender, income, education, COVID-19 history, frequency of PCR testing, and reasons for testing were analysed. Anxiety levels were measured using the Coronavirus Anxiety Scale, and data were analysed using descriptive statistics, Mann-Whitney U, Kruskal-Wallis, and Spearman correlation tests. Results showed that individuals who underwent PCR testing had significantly higher levels of anxiety than those who did not. Voluntary testers reported higher levels of anxiety than those required to be tested for work. However, those who had been tested 1-2 times had higher anxiety than those who had been tested more frequently, suggesting that familiarity with the process may reduce anxiety. Female participants were more anxious than males, while income and education level had no significant effect. Those who obtained COVID-19 information from the internet had lower anxiety than those who used mobile applications. In addition, vaccinated individuals showed higher anxiety, possibly due to concerns about side effects or vaccine effectiveness. In conclusion, there is a significant association between PCR testing and COVID-19 anxiety. Frequency of testing, reasons for testing and sources of information influence anxiety levels. To mitigate this, health authorities should improve guidance and support for individuals undergoing PCR testing to help reduce associated anxiety.